Effectiveness of Pilates Exercise in Reducing Chronic Low Back Pain in Postmenopausal Women: An Experimental Study - Ismaningsih; Siti Muawanah (POLTEKKES KEMENKES PONTIANAK, 2024)
Low back pain (LBP) is the leading cause of disability in the world, and its prevalence is increasing faster than other pain conditions. Post-menopausal women are very susceptible to experiencing low back pain, which refers to pain or discomfort in the lower back area without a structural cause or specific underlying pathology. Low back pain is experienced by twice as many women as men, and this difference becomes even greater during menopause. Changes in the hormone oestrogen are an important contributor to this painful condition. Pilates exercise can aim to reduce lower back pain through a combination of strengthening, flexibility, and improving body posture. This research aims to determine the effectiveness of Pilates exercise in reducing chronic low back pain in post-menopausal women. This research uses pre- and post-experimental methods with a sample of 10 people. , and evaluation measurements were carried out using the Visual Analogue Scale (VAS). in this treatment group, a normality test was used using the Shapirowilk test, and then an influence test was carried out using the Wilcoxon. The results of the study showed that the mean VAS value before was 620 ± 0.4216 and the value after was 260 ± 0.1075 with a P value = 0.005, which means it shows significant results. That there is a significant effect before and after treatment Pilates exercise intervention to reduce pain in women with post-menopausal chronic low back pain.